#### Answer

$-6\frac{1}{12}$

#### Work Step by Step

$6\frac{2}{3}+(-12\frac{3}{4})$
$=6\frac{2}{3}-12\frac{3}{4}$
$=-12\frac{3}{4}+6\frac{2}{3}$
$=-(12\frac{3}{4}-6\frac{2}{3})$
$=-(12\frac{9}{12}-6\frac{8}{12})$
$=-6\frac{1}{12}$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

$-6\frac{1}{12}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.